Pengaruh Pemberian Edukasi Gizi Terhadap Pengetahuan dan Sikap Calon Pengantin dalam Pencegahan Stunting di KUA Kabupaten Tana Toraja: Effect of Nutrition Education on Knowledge and Attitudes of Prospective Bride and Groom in Preventing Stunting at KUA Tana Toraja Regency - Nur Pratiwi Patata; Haniarti Haniarti; Usman Usman (Jurnal Sains dan Kesehatan, 2021)
Stunting is a condition of failure to thrive in children (body and brain growth) malnourished for a long time. Stunting in children can prevent pregnancy when a child is two years old, or also known as the first 1000 days of life, Tana Toraja Regency is one of the 10 Stunting Emergency Districts, where Tana Toraja is in third place after Enrekang and Sinjai. Therefore, the purpose of this study was to see the effect of nutrition education on the knowledge and attitudes of the bride and groom in preventing stunting. In Tana Toraja, the method used in this study is a quasi-experimental method, with a One-group pre-post test design This research shows that there is a change in the knowledge and attitudes of the prospective bride and groom after being given nutrition education, where on average the respondents have started to improve their diet for pregnancy from the nutrition education that has been given before.